Diagnostic role of coronary CT angiography in paroxysmal or first diagnosed atrial fibrillation. Issue 1 (18th May 2021) - Rottländer, Dennis; Saal, Martin; Degen, Hubertus; Gödde, Miriel; Horlitz, Marc; Haude, Michael
Abstract : Objectives: The presence of coronary artery disease (CAD) in patients hospitalised with paroxysmal or first diagnosed atrial fibrillation (AF) has major implications for antithrombotic therapy and cardiovascular event rate. Coronary CT angiography (CCTA) is a feasible tool to identify patients with concealed CAD. We aimed to evaluate the diagnostic role of early CCTA in patients hospitalised with paroxysmal or first diagnosed AF. Methods: In a 5-year single-centre retrospective analysis, 566 patients with paroxysmal or first diagnosed AF who underwent CCTA were enrolled to investigate the presence of CAD. Results: In patients with paroxysmal or first diagnosed AF, CCTA revealed CAD (coronary artery stenosis ≥50%) in 39.2%. Cardiac catheterisation was performed in 31.6%, confirming CAD in 13.1% of all patients. In 8.0% percutaneous coronary intervention and in 0.5% coronary artery bypass grafting was performed. In patients with paroxysmal or first diagnosed AF: (1) angina pectoris per se does not predict CAD; (2) multivariable regression analysis revealed age, male sex and diabetes as risk factors for CAD in AF; (3) Framingham Risk Score for coronary heart disease and CHA2 DS2 -VASc-Score were relevant risk scores of CAD and (4) the classification of Coronary Artery Calcium score reference values according to the Multi-Ethnic Study of Atherosclerosis was a predictor of CAD. Conclusion: Patients with paroxysmal or first diagnosed AF are at risk for CAD, while CCTA is a feasible diagnostic tool for CAD. We recommend to integrate CT calcium scoring and CCTA into the diagnostic workup of patients with new-onset or paroxysmal AF.